2023
DOI: 10.1093/neuonc/noad119
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial of metabolic imaging-guided dose escalation of radio-chemotherapy in patients with newly diagnosed glioblastoma (SPECTRO GLIO trial)

Abstract: PURPOSE Glioblastoma (GBM) systematically recurs after a standard 60 Gy radio-chemotherapy regimen. Since Magnetic Resonance Spectroscopic Imaging (MRSI) has been shown to predict the site of relapse, we analyzed the effect of MRSI-guided dose escalation on overall survival (OS) of patients with newly diagnosed GBM. PATIENTS AND METHODS In this multicentric prospective phase III trial, patients who had undergone biopsy or sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Additionally, MR spectroscopy might be somewhat less suitable for boost delineation compared to FET PET. An intriguing aspect of the study's results is the high OS outcome observed in the control cohort, as noted by Shu et al in a letter [42] , and the absence of a difference in the rate of radiation necrosis [40] . Compared to these results, Tsien et al (2019) presented encouraging outcomes regarding dose-escalation in their study [11] .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, MR spectroscopy might be somewhat less suitable for boost delineation compared to FET PET. An intriguing aspect of the study's results is the high OS outcome observed in the control cohort, as noted by Shu et al in a letter [42] , and the absence of a difference in the rate of radiation necrosis [40] . Compared to these results, Tsien et al (2019) presented encouraging outcomes regarding dose-escalation in their study [11] .…”
Section: Discussionmentioning
confidence: 87%
“…Notably, the 1-year survival rate stood at 92 %, with a median OS of 20 months observed among the 13 patients who had received a radiation boost targeting both hypercellular and hyperperfused tumor regions [19] . The most recently published trial exploring dose escalation is the SPECTRO GLIO trial using a slightly different approach by utilizing MRI spectroscopy to define the region which should receive dose escalation to 72 Gy [40] . Median OS and median PFS was 22.6 months and 22.2 months, and 8.6 and 7.8 months, in the cohort with and without dose escalation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in accurately identifying tumor margins, which may extend into surrounding brain tissue undetected by standard imaging, poses a significant challenge. Whole-brain MRSI has been shown to predict relapse sites post-radiotherapy, enhancing the precision of treatment planning [ 2 , 14 ]. The ability of MRSI to detect tumor infiltration more sensitively and precisely than traditional MR imaging allows for more accurate radiation targeting, potentially increasing survival by focusing on both the primary tumor and high-risk recurrence areas.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study on MRSI-guided dose escalation demonstrates the advantage of 3D whole-brain MRSI, highlighting its potential to improve glioblastoma management by customizing radiation therapy to each patient’s tumor metabolism. This approach aimed to improve disease management while minimizing radiation exposure to healthy tissue [ 2 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying these areas of restricted diffusion may serve to focus treatment on active tumor tissue. The use of additional information from biological imaging such as [ 18 F]FET (fluoroethyl-l-tyrosine) positron emission tomography/computed tomography (PET/CT) provides a molecular evaluation of malignant abnormalities [11] leading to a more refined analysis of tumoral behavior. A number of studies have proven the clinical value of amino acid tracers, such as [ 18 F]FET PET/CT, to determine the extent of cerebral gliomas for treatment planning [5], the detection of tumor recurrence, and the estimation of prognosis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%